The Effect of Internet Advertising and Content Marketing on Online Purchasing Decisions Through Customer Trust at Prinperpack In Sukabumi City - Muflihan, Elgin; Pranowo, Agus Setyo; Hannan, Sufrin (Peneliti.net, 2024)
This study explores the influence of Internet Advertising and Content Marketing on online purchasing decisions through customer trust at Prinperpack in Sukabumi City. The background of this study is based on the significant development of digital printing in recent years, which allows personalization and customization of products at a relatively low cost. Prinperpack, a company that focuses on digital printing, experienced fluctuations in income and number of consumers during the period March-September 2023. This decline is thought to be caused by the lack of Internet advertising and low quality marketing content. The research method used is quantitative with data collection through questionnaires distributed to 246 respondents from Prinperpack consumers in Sukabumi City. The results of the validity test show that most of the items in the Internet Advertising, Content Marketing, and Purchasing Decision variables are valid, but some items are invalid and need to be improved. The results of the study indicate that both Internet Advertising and Content Marketing have a significant influence on purchasing decisions, both directly and through customer trust. Customer trust plays a very important mediating role in influencing purchasing decisions. This study provides important insights for digital printing companies and other creative industries in developing effective marketing strategies to increase consumer trust and purchasing decisions.